Low temperature cross-linked, high performance polymer gate dielectrics for solution-processed organic field-effect transistors1. Issue 32 (28th August 2015) - Li, Shengxia; Feng, Linrun; Zhao, Jiaqing; Guo, Xiaojun; Zhang, Qing
<x xml:space="preserve">Abstract</x> Thermal cross-linking the bi-functional polymer thin-films at low temperature for gate dielectric application in solution processed organic field-effect transistors.